Spontaneous vaginal expulsion of a large uterine leiomyoma 10 weeks after a cesarean delivery - case report - Borges,Ana Catarina (2021)
Abstract Uterine leiomyomas are the most frequently benign smooth muscle tumor of uterus in reproductive age women and may negatively affect fertility and pregnancy outcomes. True prevalence of leiomyomas in pregnancy seems to be underestimated and its growth pattern during pregnancy remains controversial. Despite most leiomyomas present in pregnancy as an asymptomatic incidental finding, it can manifest with pain or discomfort due to torsion or degeneration. Until now, few studies reported cases of postpartum spontaneous vaginal expulsion of leiomyomas. Here we present the progression of a large hybrid leiomyoma through pregnancy and its spontaneous vaginal expulsion 10-weeks after cesarean delivery.